Acceptability of the 6-PACK falls prevention program: A pre-implementation study in hospitals participating in a cluster randomized controlled trial - Barker, A.; Morello, R.; Ayton, D.; Hill, Keith; Brand, C.; Livingston, P.; Botti, M. (Public Library of Science, 2017)
There is limited evidence to support the effectiveness of falls prevention interventions in the acute hospital setting. The 6-PACK falls prevention program includes a fall-risk tool; 'falls alert' signs; supervision of patients in the bathroom; ensuring patients' walking AIDS are within reach; toileting regimes; low-low beds; and bed/chair alarms. This study explored the acceptability of the 6-PACK program from the perspective of nurses and senior staff prior to its implementation in a randomised controlled trial. A mixed-methods approach was applied involving 24 acute wards from six Australian hospitals. Participants were nurses working on participating wards and senior hospital staff including: Nurse Unit Managers; senior physicians; Directors of Nursing; and senior personnel involved in quality and safety or falls prevention. Information on program acceptability (suitability, practicality and benefits) was obtained by surveys, focus groups and interviews. Survey data were analysed descriptively, and focus group and interview data thematically. The survey response rate was 60%. Twelve focus groups (n = 96 nurses) and 24 interviews with senior staff were conducted. Falls were identified as a priority patient safety issue and nurses as key players in falls prevention. The 6-PACK program was perceived to offer practical benefits compared to current practice. Nurses agreed fall-risk tools, low-low beds and alert signs were useful for preventing falls (>70%). Views were mixed regarding positioning patients' walking aid within reach. Practical issues raised included access to equipment; and risk of staff injury with low-low bed use. Bathroom supervision was seen to be beneficial, however not always practical. Views on the program appropriateness and benefits were consistent across nurses and senior staff. Staff perceived the 6-PACK program as suitable, practical and beneficial, and were open to adopting the program. Some practical concerns were raised highlighting issues to be addressed by the implementation plan.